2008
DOI: 10.1007/s12185-008-0210-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of four novel mutations in F5 associated with congenital factor V deficiency

Abstract: Coagulation factor V (FV) deficiency is a rare bleeding disorder characterized by low coagulant and antigen levels of FV with bleeding symptoms ranging from mild to severe. Only a limited number of mutations have been reported because of the large size of the factor V gene (F5) as well as the low prevalence. In this study, we have identified four novel mutations in F5 in five unrelated patients with congenital FV deficiency. All the patients, including two with undetectable FV activity, were asymptomatic and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…In summary, we investigated the p.Phe218Ser and p.Gly304Glu missense mutations of the F5 gene in 2 Chinese families, in which the p.Phe218Ser mutation was previously reported by Kanaji et al [15]. In our study, we revealed that the p.Phe218Ser and p.Gly304Glu F5 variants are probably deleterious and responsible for the reduction in FV:C and FV:Ag levels.…”
Section: Discussionsupporting
confidence: 63%
“…In summary, we investigated the p.Phe218Ser and p.Gly304Glu missense mutations of the F5 gene in 2 Chinese families, in which the p.Phe218Ser mutation was previously reported by Kanaji et al [15]. In our study, we revealed that the p.Phe218Ser and p.Gly304Glu F5 variants are probably deleterious and responsible for the reduction in FV:C and FV:Ag levels.…”
Section: Discussionsupporting
confidence: 63%
“…Considering the mutation of F5 in this patient, there were no detectable levels of FV antigens in plasma, whereas, FV protein was weakly detected in platelet lysate 5 . In this study, F5 mRNA expression level in F5 (mut/mut) HLCs was similar to that of positive control in this study (Figure 3C).…”
Section: Discussionsupporting
confidence: 77%
“…Coagulation tests before surgery revealed that prothrombin time‐International Normalized Ratio (PT‐INR) was 4.41 and activated partial thromboplastin time (APTT) was 133.2 seconds (27.0‐43.0 seconds). A blood test showed that FV clotting activity was <3% (normal range: 70%‐135%) and FV antigen was less than 2% (normal average: 60%‐150%) as previously reported 5 . The study protocol was reviewed and approved by the institutional review board of the Ethics Committee of the Kurume University School of Medicine, and the patient signed an informed consent form in accordance with the Helsinki Declaration.…”
Section: Methodsmentioning
confidence: 54%
“…Even though their FV defects were caused by the same pathogenic mutation, only two patients presented bleeding symptoms, suggesting a poor association between clinical symptoms of FV deficiency and the location of the mutation. Kanaji et al 19 revealed that the two probands with p.Phe190Ser did not share the same haplotype, and thus inferred that p.Phe190Ser may be a mutational hotspot. In our cohort, however, haplotype analysis revealed the founder effects.…”
Section: Discussionmentioning
confidence: 99%